Numerical Treatment for n th Order Linear Functional-Differential Equations Using Nyström's Method (Journal of the College of Basic Education, 2022)
The paper presents a proposed method with algorithms written in Matlablanguage for solving a system of linear functional-differential equationsnumerically using fifth-order-six-stage Nyström ’s method. This method hasbeen developed to find the numerical evolutions for three types (retarded,neutral and mixed) of n th order linear functional differential equations.Comparison between the numerical and exact results has been given for threenumerical examples for solving three types of linear functional differentialequations. Finally, the results are arranged in tabulated form and suitablegraphing is given for the examples.